Penerapan Etika Bisnis dalam Perspektif Islam pada Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Transaksi Jual Beli di Pasar Lama Baturaja, Kabupaten Ogan Komering Ulu - Anggun Citra Abadi; Zuul Fitriani Umari; Zulfikri, Zulfikri (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to determine the application and understanding of business ethics in the Islamic perspective on Micro, Small and Medium Enterprises (UMKM) in the Old Baturaja market, Ogan Komering Ulu Regency. The data collection method in this study uses qualitative methods. There are two types of data that researchers use in this study, namely primary data and secondary data. In this research, the data techniques used include observation, interviews and documentation. The respondents in this study were 10 UMKM traders in the Old Baturaja market. Based on the results of this study it can be concluded that traders in the Old Baturaja market still lack understanding of the ethics of buying and selling and some of them also consider the application of buying and selling ethics is not very important in trading. The understanding of traders in the Old Baturaja market is still very limited, most of them think that lying in buying and selling is like a culture. Because by being less honest or lying they can minimize their losses and get more profit. However, some of them fulfill the ethics of buying and selling that are good and right. Traders in the Old Baturaja market have not fully implemented the ethics of buying and selling properly. Such as honest trading ethics, not hoarding goods, prioritizing customer satisfaction, it has not been fully implemented by traders so that there are still buyers who feel disappointed. However, the ethics of buying and selling, namely suk.